Novel trends with biologics in inflammatory bowel disease: sequential and combined approaches. (April 2021) - Privitera, Giuseppe; Pugliese, Daniela; Lopetuso, Loris Riccardo; Scaldaferri, Franco; Neri, Matteo; Guidi, Luisa; Gasbarrini, Antonio; Armuzzi, Alessandro
Inflammatory bowel disease (IBD) management has changed dramatically over the past 20 years, after the introduction of targeted biological therapies. However, the impact of these new drugs in changing the natural history of disease is still under debate. Recent evidence seems to suggest that the extent of their efficacy might be, at least partially, dependent on the timing of their introduction and on the subsequent management strategy. In this complex landscape, the potential role for a more dynamic approach with treatments based on sequencing and combining targeted therapies has been explored only minimally so far. In this review, we aim to explore the potential biological rationale behind the use of sequential and combination therapies in IBD, to summarise the current knowledge on this topic and to propose a management algorithm that combines these notions.